Nutritional Responses of Rats to Diets Based on Chickpea (Cicer arietinum L.) Seed Meal or Its Protein Fractions - Tavano, Olga Luisa; da Silva, Sinezio Inacio; Demonte, Aureluce [UNESP]; Neves, Valdir Augusto [UNESP] (Amer Chemical Soc, 2008)
The aim of this study was to isolate the protein fractions from chickpea, var. IAC-Marrocos, as well as to evaluate its in vivo nutritional protein quality. Among the proteins, albumins showed better nutritional value in the in vivo assays and amino acid contents, despite their higher trypsin inhibitor contents. Trypsin inhibitors were found to be heat labile in all samples, but the digestibility results for unheated and heated flour and albumins suggest that their contents are not very decisive. The PER values for casein (not supplemented) were very similar to those of heated flour and unheated or heated albumin and total globulins. The albumin and glutelin fractions showed the best results for PDCAAS, however, lower than those of casein. Despite the high digestibility of the globulin the very low essential amino acid content lowered its PDCAAS, and it had the lowest values.
Keywords: Chickpea; protein fractions; biological assays; protein quality; protein digestibility; PDCAAS